Transpeptidase-mediated incorporation of D-Amino Acids into bacterial peptidoglycan - Lupoli, Tania J. (2011)
The beta-lactams are the most important class of antibiotics in clinical use. Their lethal targets are the transpeptidase domains of penicillin binding proteins (PBPs), which catalyze the crosslinking of bacterial peptidoglycan (PG) during cell wall synthesis. The transpeptidation reaction occurs in two steps, the first being formation of a covalent enzyme intermediate and the second involving attack of an amine on this intermediate. Here we use defined PG substrates to dissect the individual steps catalyzed by a purified E. coli transpeptidase. We demonstrate that this transpeptidase accepts a set of structurally diverse D-amino acid substrates and incorporates them into PG fragments. These results provide new information on donor and acceptor requirements as well as a mechanistic basis for previous observations that non-canonical D-amino acids can be introduced into the bacterial cell wall.